Communication research using BigData methodology. - López-Cantos, F. (Revista Latina de Comunicación Social, 2015)
Introduction: Digital technologies are enabling new tools and analysis methodologies in the field of communication, as well as in other research areas. In this document, we approach aspects related to communication research using the Big Data methodology, which is generating much expectation and showing good results in other scientific areas. Methodology: A set of articles were used as corpus for this work and we applied the Big Data analysis and representation techniques as contents analysis methodology over this sample in order to evaluate its relevance and effectiveness. Conclusions: As a result of our study, we can conclude that this methodology can be useful in our field of knowledge, but it has a limited effectiveness though.